Time Dynamics of Water Balance Components in the Psel River Basin - Лук’янець, Ольга Іванівна; Гребінь, Василь Васильович (Київський національний університет імені Тараса Шевченка, 2021)
In the article, in order to identify the generalized role of changes that occurred in the Psel River basin with such climatic indicators as air temperature, amount of precipitation, their form of precipitation, the structure of water bodies feeding, as well as water flow in the modern period, the average water balance for a long-term period was calculated the Psel river basin near the town of Gadyach. In general, the water balance equation shows the ratio of water input and consumption within a river basin, taking into account changes in its reserves over a selected time interval and allows one to assess the relationship of its individual components. In the article identifies changes in the ratio between the inflow (amount of precipitation) and consumption of water (total evaporation and runoff) for two periods – the climatic norm of 1961-1990 and modern 1990-2019. Analysis of the temporal dynamics of the water balance components of the Psel river basin showed that the values of the water balance components within the Psel river basin near the town of Gadyach in the modern period have decreased in comparison with the period of the climatic norm – the amount of precipitation by 6,2%, water flow by 17,5%, evapotranspiration by 1,8%. But, analyzing the relationship between the inflow and outflow of water in the basin for the two study periods 1961-1990 and 1990-2019, it can be stated that during the period of the climatic norm, the percentage of water flow from the total precipitation was greater (coefficient water flow 16.2%) than in the modern period (coefficient water flow 14.2%). With regard to total evaporation in water-balance ratios, its share in the water-balance ratio has increased over the modern period (1990-2019). If during the period of climatic normal (1961-1990) the aridity coefficient was 83.8%, then in the modern period, it is 85.8%. That is, the “redistribution” of the water volumes of atmospheric precipitation took place towards the total evaporation with a decrease in the volume of water used to form the water runoff. For the basin of the river Psel – the city of Gadyach in the modern period on the average ≈ 11 mm (or ≈ 130000000 m3) evaporate instead of replenishment of water resources. In the previous period of 1961-1990, on the contrary, ≈ 12 mm (or 136000000 m3) did not evaporate, but flowed into the water bodies of the basin.

Аналіз часової динаміки водно-балансових складових в басейні р. Псел показав, що хоча величини складових водного балансу в межах басейну р. Псел – м. Гадяч в сучасний період (1990-2019 рр.) зменшилися у порівнянні з періодом кліматичної норми (1961-1990 рр.) – кількість атмосферних опадів на 6,2%, стік води на 17,5%, сумарне випаровування на 1,8%, але, аналізуючи співвідношення між надходженням та витрачанням води в басейні за два досліджувані періоди, можна констатувати, що в період кліматичної норми відсоток стоку води від суми атмосферних опадів був більшим (коефіцієнт стоку води 16,2%), ніж в сучасний період (коефіцієнт стоку води 14,2%). Щодо сумарного випаровування у водно-балансових співвідношеннях, то його частка у водно-балансовому співвідношенні за сучасний період (1990-2019 рр.) збільшилася. Якщо в період кліматичної норми (1961-1990 рр.) коефіцієнт посушливості був 83,8%, то в сучасний період – 85,8%. Тобто відбувся «перерозподіл» об’ємів води атмосферних опадів в бік сумарного випаровування зі зменшенням об’ємів води, що йдуть на формування стоку води.
Часова динаміка водно-балансових складових в басейні р. Псел
Keywords: річковий басейн; складові водного балансу; багаторічні зміни; коефіцієнт стоку; коефіцієнт посушливості; р. Псел; river basin; water balance components; long-term changes; runoff coefficient; aridity coefficient; Psel River